Progressive Deafness-Dystonia due to SERAC1 Mutations: A Study of 67 cases - Maas, RR (2017)
OBJECTIVE: 3-Methylglutaconic aciduria, dystonia-deafness, hepatopathy, encephalopathy, Leigh-like syndrome (MEGDHEL) syndrome is caused by biallelic variants in SERAC1. METHODS: This multicenter study addressed the course of disease for each organ system. Metabolic, neuroradiological, and genetic findings are reported. RESULTS: Sixty-seven individuals (39 previously unreported) from 59 families were included (age range = 5 days-33.4 years, median age = 9 years). A total of 41 different SERAC1 variants were identified, including 20 that have not been reported before. With the exception of 2 families with a milder phenotype, all affected individuals showed a strikingly homogeneous phenotype and time course. Severe, reversible neonatal liver dysfunction and hypoglycemia were seen in >40% of all cases. Starting at a median age of 6 months, muscular hypotonia (91%) was seen, followed by progressive spasticity (82%, median onset = 15 months) and dystonia (82%, 18 months). The majority of affected individuals never learned to walk (68%). Seventy-nine percent suffered hearing loss, 58% never learned to speak, and nearly all had significant intellectual disability (88%). Magnetic resonance imaging features were accordingly homogenous, with bilateral basal ganglia involvement (98%); the characteristic "putaminal eye" was seen in 53%. The urinary marker 3-methylglutaconic aciduria was present in virtually all patients (98%). Supportive treatment focused on spasticity and drooling, and was effective in the individuals treated; hearing aids or cochlear implants did not improve communication skills. INTERPRETATION: MEGDHEL syndrome is a progressive deafness-dystonia syndrome with frequent and reversible neonatal liver involvement and a strikingly homogenous course of disease. Ann Neurol 2017;82:1004-1015